Taxonomic review of Saguinus mystax (Spix, 1823) (Primates, Callitrichidae), and description of a new species - Lopes, Gerson Paulino; Rohe, Fábio; Bertuol, Fabrício; Polo, Erico; Lima, Ivan Junqueira; Valsecchi, João; Santos, Tamily Carvalho Melo; Nash, Stephen D.; Silva, Maria Nazareth Ferreira da; Boubli, Jean P.; Farias, Izeni Pires; Hrbek, Tomas (PeerJ, 2023)
Although the Amazon has the greatest diversity of primates, there are still taxonomic uncertainties for many taxa, such as the species of the Saguinus mystax group. The most geographically broadly distributed and phenotypically diverse species in this group is S. mystax, and its phenotypic diversity has been recognized as three subspecies—S. mystax mystax, S. mystax pileatus and S. mystax pluto—with non-overlapping geographic distributions. In this sense, we carried out an extensive field survey in their distribution areas and used a framework of taxonomic hypothesis testing of genomic data combined with an integrative taxonomic decision-making framework to carry out a taxonomic revision of S. mystax. Our tests supported the existence of three lineages/species. The first species corresponds to Saguinus mystax mystax from the left bank of the Juruá River, which was raised to the species level, and we also discovered and described animals from the Juruá–Tefé interfluve previously attributed to S. mystax mystax as a new species. The subspecies S. m. pileatus and S. m. pluto are recognized as a single species, under a new nomenclatural combination. However, given their phenotypic distinction and allopatric distribution, they potentially are a manifestation of an early stage of speciation, and therefore we maintain their subspecific designations.
Keywords: Platyrrhini; Phylogeny; New world monkeys; New species; Cryptic; Amazonian tamarin; Phylogenomic; Geographic distribution; Taxonomy; Species